Studi Efek Kerr Untuk Pengujian Tingkat Kemurnian Aquades, Air PAM dan Air Sumur - Sukarsono, Kristantyo; Marhaendrajaya, Indras; Firduasi, K. Sofjan (BERKALA FISIKA, 2008)
In this research was discussed about the ratio of purity level of aquades, running water, and well water by using the Kerr effect. Several substances being used are sugar solutions with the concentration of 10%, 20%, 30%, 40% and 50% for linearity testing, salt solutions with the concentration of 10%, 30% and 50% for the testing of ionic response which be infested by some dipoles of H2O molecules in the salt solution toward the external electrical field, and also aquades, running water and well water as the water samples having the different purity. The external electrical field being given in the substances from zero to 9×105 V/m and awakened by conducting the direct current of electric on the parallel plates. A light beam being used is a diode laser with λ = 645 nm. The result of research was showing that the presence of external electrical field causing the difference of polarization angle indicating the purity level of water kinds since influenced by ions in the water. Based on the ions containing in it have been known that the value of aquades purity is 4 ppm, the value of running water purity is 108 ppm and the value of well water purity is 190 ppm. So, aquades is purer than running water and running water is purer than well water. The average value of polarization angle of aquades, running water, and well water is approximately 0,50º, 0.25º and -0,25º respectively. Key words: Kerr Effect, electrical field, polarization angle